The Vertebrate Brain, Evidence of Its Modular Organization and Operating System: Insights into the Brain's Basic Units of Structure, Function, and Operation and How They Influence Neuronal Signaling and Behavior - Baslow, Morris H. (Frontiers in Behavioral Neuroscience, 2011)
The human brain is a complex organ made up of neurons and several other cell types, and whose role is processing information for use in eliciting behaviors. However, the composition of its repeating cellular units for both structure and function are unresolved. Based on recent descriptions of the brain’s physiological “operating system”, a function of the tri-cellular metabolism of N-acetylaspartate (NAA) and N-acetylaspartylglutamate (NAAG) for supply of energy, and on the nature of “neuronal words and languages” for intercellular communication, insights into the brain’s modular structural and functional units have been gained. In this article, it is proposed that the basic structural unit in brain is defined by it’s physiological operating system, and that it consists of a single neuron, and one or more astrocytes, oligodendrocytes and vascular system endothelial cells. It is also proposed that the basic functional unit in the brain is defined by how neurons communicate, and consists of two neurons and their interconnecting dendritic-synaptic-dendritic field. Since a functional unit is composed of two neurons, it requires two structural units to form a functional unit. Thus, the brain can be envisioned as being made up of the three-dimensional stacking and intertwining of myriad structural units which results not only in its gross structure, but also in producing a uniform distribution of binary functional units. Since the physiological NAA-NAAG operating system for supply of energy is repeated in every structural unit, it is positioned to control global brain function.